GE_GERICHTE P/1313/2019 vom 28. April 2022 - GE Cour de justice (2022)
PARTIE À LA PROCÉDURE;QUALITÉ POUR AGIR ET RECOURIR;DOMMAGE;LÉSÉ;INFRACTIONS CONTRE LE PATRIMOINE | CPP.382; CPP.115; CPP.118; CP.146; CP.158